2013
DOI: 10.1002/ijc.28252
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CACNA2D3 as a putative tumor suppressor gene in the development and progression of nasopharyngeal carcinoma

Abstract: Apart from b-catenin accumulation, loss of 3p21 is one of the most frequent genetic alterations in numerous malignancies including nasopharyngeal carcinoma (NPC). Herein, we characterized a novel candidate tumor suppressor gene (TSG) CAC-NA2D3, a voltage-dependent subunit alpha 2 delta 3 of a calcium channel complex. Downregulation of CACNA2D3 was frequently detected in primary NPCs and NPC cell lines compared with their nontumorigenic counterparts. Attenuated CACNA2D3 expression may be associated with loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
3
28
0
2
Order By: Relevance
“…m m [43] ADAMTS9 m m [55] ADAMTS18 m m [56] CACNA2D3 m m [57] CADM1 m m [26,29] CCNA1 m m [58] CDH4 m m [59] CDH11 m m [41] CHFR m m [24,29] CMTM3 m m [45] CMTM7 m m [54] DACT1 m Verified in the current study -…”
Section: Adamts8supporting
confidence: 59%
“…m m [43] ADAMTS9 m m [55] ADAMTS18 m m [56] CACNA2D3 m m [57] CADM1 m m [26,29] CCNA1 m m [58] CDH4 m m [59] CDH11 m m [41] CHFR m m [24,29] CMTM3 m m [45] CMTM7 m m [54] DACT1 m Verified in the current study -…”
Section: Adamts8supporting
confidence: 59%
“…Downregulation of CACNA2D3 was shown by our findings to be a common feature of glioma tissue. Downregulation of CACNA2D3 has been correlated with extensive promoter hypermethylation in nasopharyngeal carcinoma cells [51] and in gastric carcinoma cells [23]. We also found that downregulation of CACNA2D3 in high-grade glioma cells and tissue was accompanied with increased methylation.…”
Section: Discussionsupporting
confidence: 62%
“…Promoter methylation of tumor suppressor genes (TSGs), such as calcium channel voltage-dependent alpha 2/delta subunit 3 ( CACNA2D3 ) and cadherin 4 ( CDH4 ), may play a crucial role in NPC development and progression (Wong et al, 2013, Du et al, 2011). Localized in human chromosomal region 3p21.3, the RAS association domain family protein 1A ( RASSF1A ) is an important TSG involved in multiple biological functions, including cell cycle regulation, microtubule stabilization, and apoptosis (Allen et al, 2007, Agathanggelou et al, 2005, Burbee et al, 2001).…”
Section: Introductionmentioning
confidence: 99%